Bremermanns Limit in cGh-Physics (Global Journal of Science Frontier Research, 2024)
Do physical laws limit the speed of all data processing systems manmade as well as biological A positive answer proposed by H J Bremermann in 1962 should be corrected to make it compatible with Einstein s theory of gravity aka general relativity or GR As a result the Bremermann s limit proportional to mass M of the computer Mc2 h M gram 1047 bits per second should be replaced by the absolute limit c5 Gh 1 2 1043 bits per second where the universal constants c G and h are the speed of light the gravitational constant and Planck s constant
Keywords: data processing rate; bremermann's limit; general relativity; universal physical constants